Problematika Menulis Karangan Sederhana Bahasa Jerman - Sri Wahyuni; Misnawaty Usman; Syukur Saud (Universitas Negeri Makassar, 2023)
Abstract. The purpose of this study was to find out the problem of writing simple essays in German for class XI student of SMA Negeri 1 Takalar. This research is a descriptive qualitative research. The source of the research data was class XI student of SMA Negeri 1 Takalar with a sample of 50 students. The research data is in the form of a questionnaire. The result of this study indicate that the students problem in writing simple essays in German are lack of vocabulary mastery, lack of understanding of verb conjugations, lack of ideas, lack of confidence, lack of facilities and infrastructure and not mastery of German grammar.Keywords: Problematic, Writing, Essay